Concise Synthesis of the Hexasaccharide Repeating Unit of the Capsular Polysaccharide of Klebsiella K19 Strain - Sahaji, Samim; Shit, Pradip; Misra, Anup Kumar (Synthesis, 2023)
A convergent [4+2] stereoselective block glycosylation strategy has been developed for the synthesis of the hexasaccharide repeating unit of the capsular polysaccharide of Klebsiella K19 strain in very good yield. The p-methoxybenzyl (PMB) group was used as a temporary alkyl protecting group, which was removed by tuning the glycosylation conditions. A thioglycoside was used as a glycosyl acceptor in an orthogonal glycosylation reaction. A late-stage TEMPO-mediated selective oxidation of a primary hydroxyl group into carboxylic acid allowed incorporation of the d-glucuronic acid moiety in the hexasaccharide. A combination of N-iodosuccinimide (NIS) and perchloric acid supported over silica (HClO4–SiO2) was used as a thiophilic promoter for the activation of thioglycosides. HClO4–SiO2 was also used as a solid acid activator for a glycosyl trichloroacetimidate derivative.
Keywords: carbohydrates; glycosylation; glycosides; oligosaccharides; synthesis; Klebsiella